2007
DOI: 10.1159/000098481
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Estimation Using Bioelectrical Impedance

Abstract: Background/Aims: Although childhood obesity is a major problem, routine assessment methods do not reflect fat mass. Body mass index, which is most commonly used, gives an indication of weight for height and not a degree of adiposity. Methods: Bioelectrical impedance and dual-energy X-ray absorptiometry (DEXA) were used in a group of obese children to assess body fat. Results: Comparison between DEXA and commercial bioelectrical impedance scales in 46 children showed a highly significant correlation (R = 0.944,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
(9 reference statements)
2
19
0
Order By: Relevance
“…In our research centre, the bioelectrical impedance analyser was validated using dual-energy X-ray absorptiometry (DEXA) in overweight and obese individuals. Also, a highly linear relationship between fat mass assessed by the bioelectrical impedance method and that assessed by DEXA has been documented by others (Shafer, Siders, Johnson, & Lukaski, 2009;Shaikh, Crabtree, Shaw, & Kirk, 2007).…”
Section: Anthropometrymentioning
confidence: 66%
“…In our research centre, the bioelectrical impedance analyser was validated using dual-energy X-ray absorptiometry (DEXA) in overweight and obese individuals. Also, a highly linear relationship between fat mass assessed by the bioelectrical impedance method and that assessed by DEXA has been documented by others (Shafer, Siders, Johnson, & Lukaski, 2009;Shaikh, Crabtree, Shaw, & Kirk, 2007).…”
Section: Anthropometrymentioning
confidence: 66%
“…BP and hypertension correlates with FM, seems to be valid. Another limitation of our investigation is the missing gold standard method, such as dual energy X-ray absorptiometry [29] for FM evaluation when comparing BIA values versus BMI values. However, we have shown that BIA is able to demonstrate the acknowledged divergence of FM during puberty in healthy boys and girls, whereas this was not possible with BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Although measuring skinfold thickness is a practical method, inter-observer variability and need for qualified staff limits its widespread use and the reliability of this method in some situations. Using bioelectrical impedance (BIA) measurements to assess the quantity of body fat accumulation and segmental distribution of this fat content is considered relatively expensive when compared to measuring skinfold thickness, but determining body fat with BIA is much more practical, provides segmental distribution, and can easily be used in population screening as well as used in daily practice [19,21].…”
mentioning
confidence: 99%